Knowledge and perception on ovarian cyst among women in International Islamic University Malaysia (IIUM) Kuantan, Pahang Malaysia - Raja Idris, Raja Ibrah; Abdul Ghani, Radiah (2019)
Ovarian cyst is one of the common gynecological problem among women at the reproductive age suggesting that knowledge and perception on ovarian cyst among women is still uncertain. It is believed that a good knowledge and perception regarding ovarian cyst would motivate more women to utilize the availability of early detection and seek for treatment due to this disease always asymptomatic. Therefore, this cross-sectional study aimed to assess the knowledge and perception regarding ovarian cyst among women in International Islamic University Malaysia (IIUM) Kuantan, Pahang. The association between socio-demographic factors with knowledge and perception on ovarian cyst was also examined in this research. This study involved 123 women from various professions among IIUM Kuantan community. Self-administered questionnaires were distributed from January 2019 until March 2019. The level of knowledgeand perception has been analyzed and it was found that the knowledge and perception level on ovarian cyst among women in IIUM Kuantan was moderate which were 90.2% and 95.1% respectively. Apart from that, Analysis of Variance (ANOVA) was used to evaluate the relationship between socio-demographic in terms of age, educational background andincome with knowledge and perception on ovarian cyst. Factors that show significant association with knowledge on ovarian cyst in this study were the age group (p=0.007) and educational background (p=0.004). However, there was no significant association between socio-demographic characteristics with perception on ovarian cyst that was recorded. Inaddition, this study demonstrated that there was a significant correlation(p<0.001) between the elements of knowledge and perception regarding ovarian cyst among women in IIUM Kuantan community. Hence, it is hoped that this study can increase the information to women in IIUMKuantan and other community to take early preventive step to reduce thenumber of ovarian cyst cases.